Effect of Walnut on Lipid Profile in Obese Female in Different Ethnic Groups of Quetta, Pakistan - Mushtaq, Rehana; Rubina, Mushtaq; Tasawar, Zahida Khan (Pakistan Journal of Nutrition, 2009)
Four week controlled study was designed to observe the effect of 40 g of walnut in daily breakfast on Body Mass Index (BMI), total Cholesterol (CHO), Triglyceride (TG) High Density Lipoprotein (HDL) cholesterol and Low Density Lipoprotein (LDL) cholesterol in obese female subjects of various ethnics, i.e. Baloch (B), Pathan (P), Hazara (H) and Punjabi (PU) residing in Quetta region of Balochistan. A batch of 32 obese female subjects, 8 from each ethnic group as a control and another batch of 32 obese females 8 from each ethnic group as treated were selected. Twelve hour fasting blood samples a day after stoppage of walnut were taken from obese control and obese treated subjects. Daily walnut consumption demonstrated considerable drop in body weight in all ethnic groups residing in Quetta locality. Marked and statically significant reduction in total cholesterol was noticed in all ethnic groups i.e. 3.6% (p<0.05), 5.4% (p<0.001), 5.8% (p<0.01) and 7% (p<0.001) in B, P, H and PU groups respectively. Baloch subjects showed significant reduction of 7.8% in TG (p<0.001), similarly significant lowered TG was also observed in PU group. A significant increase (p<0.001), (p<0.05) in HDL cholesterol had been observed in B and P group respectively in walnut consuming subjects. In walnut consuming female subjects significant reduction (p<0.05), (p<0.01), (p<0.01) in LDL cholesterol levels was noted in B, P and PU subjects respectively. The positive influence of walnut on lipid profile suggests that walnut rich diet may have beneficial effects beyond changes in plasma lipid level.